An Overview of Diabetes Mellitus Patients - Rw Faiz Rifqi Imansyah; Atih Rahayuningsih; Siti Yuliharni (GLOBAL HEALTH SCIENCE GROUP, 2025)
Dietary compliance among patients with type 2 diabetes mellitus (T2DM) is a crucial aspect of disease management, yet many patients in rural areas, including the Pengarayan Health Center service area in Ogan Komering Ilir Regency, still exhibit low adherence. Several factors such as knowledge, education level, family support, and healthcare worker involvement are suspected to influence this behavior. Objective to provide an overview of the levels of knowledge, family support, healthcare worker support, and dietary compliance among T2DM patients in the working area of Pengarayan Health Center, Tanjung Lubuk Subdistrict. This was a quantitative descriptive study using a cross-sectional design. Total sampling was applied to 125 T2DM patients registered in the health center area. Data were collected using validated and reliable questionnaires measuring knowledge, family support, healthcare worker support, and dietary compliance. The study found that 63.2% of patients had low knowledge, 51.2% received good family support, and 64.0% reported support from health workers. Dietary compliance was found in 50.4% of respondents. Educational attainment showed a strong relationship with compliance, where those with higher education levels were more adherent to dietary recommendations. Knowledge level and family support play a vital role in dietary compliance among T2DM patients. Strengthening education and involving family and healthcare professionals more actively could significantly improve adherence to dietary guidelines and better disease control outcomes.